Activation Energy Determination in Case of Independent Complex Kinetic Processes - Luciano, Giorgio; Svoboda, Roman (MDPI, 2019)
Theoretically simulated kinetic data were used to evaluate the performance of the most common isoconversional methods of kinetic analysis in complex-process scenarios with two independent overlapping processes exhibiting nucleation-growth kinetics, and further expand the conclusions for the autocatalytic kinetic processes with positive asymmetry. In close-to-real-life situations all the integral isoconversional methods provided practically indistinguishable E-alpha outcomes. The Friedman and incremental modified Vyazovkin methods results in significant over- and undershoots. However, the combined utilization of the integral and differential isoconversional methods was demonstrated to greatly contribute to the interpretation of the E-alpha dependences and estimation of E-1 and E-2-the conceptual evaluation involving positions of inflection points and plateaus is introduced. The influence of the range of applied heating rates q(+) on the course of E-alpha dependences was studied. In this regard, the performance of the isoconversional methods changes significantly with both, the consistence of the shape of the complex kinetic curve and weighted presence of full overlaps of the involved sub-processes.
Stanovení aktivační energie v případě nezávislých komplexních kinetických procesů
Keywords: activation energy; complex processes; solid-state kinetics; aktivační energie; komplexní procesy; kinetika v pevné fázi